Assessment of Economic Efficiency, Effects and Risks of Digitalization Projects of Garment Industry in Russia - Kudryavtseva Tatiana Yu.; Kozhina Ksenia S.; Prause Gunnar K.; Olaniyi Eunice O. (Ural Federal University, 2025)
To increase production efficiency at industrial enterprises, various digital technologies have recently been used, which have various effects: reduction of time, money, material costs, reduction of the production cycle, productivity growth. This study aims to analyze and evaluate the efficiency of the digitalization of garment production, determine the effects and risks of a digitalization project. The digitalization project was carried out using the radio-frequency identification technology to monitor the sequential processes of garment making.This study tests a hypothesis that the use of digital technologies leads to a reduction in time losses and an increase in labor productivity. During the study, the time of the production process was measured. Further on, the possible reduction of time losses due to the introduction of digital technology under the conditions of existing production capacities is calculated. Time losses were used for additional production, which leads to a change in the company’s cash flows. As a result, the performance indicators of the investment project were calculated, and its risks were assessed using sensitivity analysis.The theoretical significance is in determining the economic indicators that are affected by the introduction of digital technology in the garment industry. The introduction of the radio-frequency identification technology makes it possible to monitor the parameters of the production process, which helped to reduce time loss by 50%, decrease the labor intensity of the product and increase the productivity of the enterprise’s personnel by 30%. The implementation of digitalization projects has risks for companies. To minimize possible risks that could arise, sustainable mitigating solutions were proffered.
Key words: garment industry; digital technologies; smart production; Industry 4.0; risk assessment; sustainable development; economic efficiency; investment impact analysis.